PENERAPAN METODE VARIABLE COSTING DALAM PERHITUNGAN HARGA POKOK PRODUKSI UNTUK MENENTUKAN HARGA JUAL - Yuda Purniawan; Imam Mas'ud; Novi Wulandari (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2019)
This research is focused on the Application of Variable Costing Methods in Calculating Cost of Production to Determine Selling Prices. The purpose of this study is 1]. To determine the cost of production according to UD. Karunia. 2]. To determine the cost of production using the variable costing method at UD. Karunia. 3]. To find out the effect of changes in the method of calculating the cost of production and determining the new selling price of profits at UD. Karunia. This research is a descriptive qualitative study. This research was conducted at UD. Karunia Banyuwangi by using primary data and secondary data. Primary data is obtained through interviews with a deep, open, and structured nature. Secondary data obtained from documents belonging to UD. Karunia. Data analysis techniques are done by data reduction, data triangulation, data presentation and conclusion drawing. The results of this study indicate that UD. Karunia use the full costing method and it is produced that the cost of producing sponge cake is Rp 4.730 per pack. The calculation using the variable costing method resulted in the cost of producing sponge cake amounting to Rp 4.121, resulting in a lower difference of Rp 609. Changes in the calculation of cost of production were made as the basis for adjusting the newselling price of sponge cake to Rp 8.000 per pack and profit decreased by Rp 2.170.405. Keywords: cost of production, selling price, variable costing